PSYCHOLOGICAL FACTORS ON PAT SOLITANO IN SILVER LININGS PLAYBOOK - Tumba, Andi Asti Riana Sari (Universitas Gunadarma, 2017)
Film is one of literary work that interesting to discuss. The images on screen told a story and language in film established firmly the connection to literature. In this research, the writer tries to analyze the major character in film by using psychological factors. As the material of the discussion, the aim of the study is to find out psychological factors that influences Pat Solitano in Silver Lining Playbook. The writer used descriptive qualitative as research method. Besides that, the writer also used some books, dictionaries and internet to collect the data about psychological factors.. The result of the study showed that Pat Solitano has influenced by his attitudes, appetites, wants, emotions, feeling and attitudes and also social motives that makes Pat Solitano turns into unstable and a motivated person toward his life. Keywords: Psychology, Character, Attitude And Human Motivation